JEMBATAN ATAU TEMBOK: TANTANGAN MODERASI BERAGAMA DALAM MEDIA SOSIAL - Syahputra, Ali (Moderatio: Jurnal Moderasi Beragama, 2024)
This study explores religious moderation on social media, which has become the main platform for disseminating information and building interactions between individuals. However, in the context of religious plurality, using social media often poses challenges to religious moderation. This study will explore the use of social media in religious moderation, whether as a bridge or as a wall in providing space for interfaith dialog. Through a qualitative approach by analyzing controversial phenomena, user perceptions, and the role of algorithms. This research aims to identify critical points that affect the success or failure of religious moderation in creating an inclusive and productive dialog space. The researcher found that the narratives on social media have become conservative, allowing the free transmission of religious views without a filter. This research suggests that moderates should be more active in filling the spiritual space of the people so that social media can be a positive bridge to promote religious moderation. The research provides practical implications by detailing findings related to positive dialog, the role of opinion leaders, and the challenge of hoaxes. This can help design better strategies and policies to promote religious moderation on social media.